A unified framework for diagnostic test development and evaluation during outbreaks of emerging infections - Madhav Chaturvedi; Denise Köster; Patrick M. Bossuyt; Oke Gerke; Annette Jurke; Mirjam E. Kretzschmar; Marc Lütgehetmann; Rafael Mikolajczyk; Johannes B. Reitsma; Nicole Schneiderhan-Marra; Uwe Siebert; Carina Stekly; et al. (Communications Medicine)
Abstract Evaluating diagnostic test accuracy during epidemics is difficult due to an urgent need for test availability, changing disease prevalence and pathogen characteristics, and constantly evolving testing aims and applications. Based on lessons learned during the SARS-CoV-2 pandemic, we introduce a framework for rapid diagnostic test development, evaluation, and validation during outbreaks of emerging infections. The framework is based on the feedback loop between test accuracy evaluation, modelling studies for public health decision-making, and impact of public health interventions. We suggest that building on this feedback loop can help future diagnostic test evaluation platforms better address the requirements of both patient care and public health.